The role of public relations in managing crises in institutions From the point of view of workers in the municipality of Riyadh - Al- Maamari, Jamal Abdullah (Journal of Humanities & Social Sciences, 2021)
The present study aimed to identify the role of public relations in managing crises in institutions from the point of view of workers in the municipality of Riyadh, and to identify the role of public relations in the early detection of the crisis. The current research used the descriptive method and the questionnaire was used as a research tool. The research sample consisted of 160 individuals working in the municipality of Riyadh, who were chosen in a simple random way. The study found that the role of public relations in crises came between (2.58- 3.95), which is a medium degree. This is due to the fact that the culture of some institutions is still absent from the role of public relations in institutions. In the field of crises detection, the arithmetic averages ranged between (3.02 - 4.22), and the axis came with a moderate degree due to the lack of joint cooperation between departments and the development of plans that would reveal crises before they happen. In the field of information availability, the arithmetic averages ranged between (3.19- 3.92). The fourth field: Communication The arithmetic averages ranged between (3.05 – 3.69). Based on the results, the researcher presented a set of recommendations and proposals to activate the role of public relations in crisis management.
Keywords: role; crisis management; public relations